Mobilisation (record) et polarisation (spectaculaire) de l’électorat écossais autour de l’enjeu de l’indépendance - Gilles Leydier (Revue Française de Civilisation Britannique)
The referendum on Scottish independence resulted in an exceptional mobilization as well as a dramatic polarization of the Scottish electorate, with nationalists and unionists emerging as the two central categories of the political debate. This article aims at analysing the voting patterns of the electorate, in relation to demographic and socio-economic factors, voters’ motivations and attitudes to risk and uncertainty.